2011
DOI: 10.1158/1940-6207.capr-11-0036
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Celecoxib to Prevent Recurrence of Nonmuscle-Invasive Bladder Cancer

Abstract: Significant morbidity and expense result from frequent recurrences of non-muscle invasive bladder cancer (NMIBC) after standard treatment, and carcinoma in situ (Tis) is a poor prognostic factor. Predicated on observational and preclinical data strongly supporting cyclooxygenase-2 (COX-2) in the pathogenesis, and the activity of COX-2 inhibitors, in bladder cancer, we conducted a randomized, double-blind, placebo-controlled trial to determine if celecoxib could reduce the time-to-recurrence (TTR) in NMIBC pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 52 publications
(60 reference statements)
1
24
0
Order By: Relevance
“…NSAIDs could suppress COX-2 expression and prevent the effects of prostaglandins. Celecoxib, the first selective COX-2 inhibitor approved by the U.S. Food and Drug Administration, has been reported to prevent carcinogenesis in both animals and humans [11,12,13]. Moreover, it has been reported that the chemotherapy, including celecoxib when used at low dose, may be able to enhance the efficacy of radiation treatment on the cancer cells [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs could suppress COX-2 expression and prevent the effects of prostaglandins. Celecoxib, the first selective COX-2 inhibitor approved by the U.S. Food and Drug Administration, has been reported to prevent carcinogenesis in both animals and humans [11,12,13]. Moreover, it has been reported that the chemotherapy, including celecoxib when used at low dose, may be able to enhance the efficacy of radiation treatment on the cancer cells [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Sabichi et al . (32) did not observe a clinical benefit of celecoxib in preventing recurrence of non-muscle-invasive bladder cancer in a randomized controlled trial, although, celecoxib had a marginally significant effect on reducing metachronous recurrences compared with placebo. However, nimesulide was capable of preventing bladder tumor recurrences in a dose-dependent manner (28).…”
Section: Discussionmentioning
confidence: 94%
“…Celecoxib, a selective COX-2 inhibitor, has been widely evaluated in numerous preclinical studies and human clinical trials for potential chemopreventive activity for cancers of colon, bladder, head and neck, skin and esophagus (Bertagnolli et al, 2006; Elmets et al, 2010; Limburg et al, 2005; Sabichi et al, 2011; Shin et al, 2013). Unfortunately, the potential for toxicity, particularly cardiac, may limit the use of COX-2 inhibitors for chemoprevention with the exception of the most high risk cohorts (Solomon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%